Identifying and Prioritizing Obstacles to the Intermediate development of Zabol City Via Chang’s Method - Majid Goodarzi; Ali Ashkboos; Behnam Mohammadi (تحقیقات کاربردی علوم جغرافیایی)
The intermediate development approach posits that vacant lands and the deteriorating structures within urban areas should be prioritized for development rather than expanding into the periphery of cities currently under construction. Acknowledging this significance, the present article endeavors to identify and prioritize the barriers to intermediate development in Zabol, utilizing Chang's technique. This applied study employs a descriptive-analytical research methodology, incorporating both library research and survey research (field studies) for data collection. The statistical population for identifying the obstacles to intermediate development comprised all residents of Zabol city in 2023. The sample size was calculated to be 384 using Cochran's formula, and a purposive sampling method was employed to gather the data. The reliability of the research instrument was assessed using Cronbach's alpha coefficient, yielding a value of 0.80. The identification of obstacles was conducted through a sample t-test in SPSS, followed by the prioritization of the identified barriers. Data were collected from existing information about the city and through a questionnaire distributed to 20 relevant experts. Subsequently, the data were analyzed using Chang's technique (AHP-FUZZY). The findings indicated that the most significant obstacle to the implementation of the intermediate development plan for Zabol city is the economic index, which received a final weight of 483.